Stabilization of the spine in the trauma victim - integrative review - Bento, Ana Filipa Gaudêncio (2021)
Goal: To identify harmful effects caused by the stabilization of the vertebral column in a trauma victim and in trauma situations without indication for stabilization of the spine in the prehospital. Method: It was perform an integrative literature review guided by research questions: is there a scientific evidence of harmful effects on trauma victims caused by spinal stabilization in prehospital care? and are there situations of trauma with no indication for stabilization of the spine? Results: We have performed a Boolean search in the electronic bases Cochrane Library and Pubmed and through the EBSCOhost engine in the databases CINAHL Plus, MEDLINE, MedicLatina, SPORTDiscus, PsycARTICLES, PsycBOOKS, Psychology and Behavioral Sciences Collection, Academic Search Complete. Twelve articles were obtained and after applying the inclusion and exclusion criteria, the sample was five articles. Conclusions: Harmful effects of spinal stabilization on the victim of trauma related to airway management, pain, discomfort and pressure injuries are described. Situations of penetrating trauma with unstable circulation and victims with gunshot injuries to the head do not require stabilization of the spine. Recommendations to support the prehospital decision regarding stabilization of the spine were collected. It is crucial for the improvement of prehospital care to integrate an individualized approach of the victim that refers to its clinical state and mechanism of injury.